Modern Corporate Finance, Investments, Taxation and Ratings - Brusov, Peter (Springer International Publishing, 2018)
This monograph is devoted to a modern theory of capital cost and capital structure created by this book's authors, called the Brusov-Filatova-Orekhova (BFO) theory, and its application to the real economy. BFO theory promises to replace the traditional theory of capital cost and capital structure by Nobel laureates Modigliani and Miller. This new theory in particular, presents a possible explanation to the causes of the recent global financial crisis. The authors of the book describe the general theory of capital cost and capital structure that can be applied to corporations of arbitrary age (or with arbitrary lifetime) and investment projects with arbitrary duration. The authors illustrate their theory with examples from corporate practice and develop investment models that can be applied by companies in their financial operations. This updated second edition includes new chapters devoted to the application of the BFO theory in ratings, banking and other areas. The authors also provide a new approach to rating methodology highlighting the need for including financial flow discounting, the incorporation of rating parameters (in particular, financial ratios) into the modern theory of capital structure - BFO theory. This book aims to change our understanding of corporate finance, investments, taxation and rating procedures. The authors emphasize that the most used principles of financial management should be changed in accordance to BFO theory.